Unlocking the potential of supply chain digitalization for enhancing enterprise green transformation performance: evidence from China - Tao Wang; Yang Shen (Humanities & Social Sciences Communications)
Abstract The supply chain is a significant source of carbon emissions for enterprises, and effectively managing this carbon footprint is a key strategy for achieving dual carbon goals and promoting sustainable development. In 2018, China launched the supply chain innovation and application pilot policy to promote supply chain digitalization (SCD), yet its actual impact on enterprise green transformation performance (EGTP) remains unclear. This study uses panel data of Chinese A-share listed companies from 2013 to 2023 as the research sample. Grounded in the practice-based view and dynamic capability theory, we employ a double machine learning method for empirical analysis. Our findings reveal that SCD significantly improves EGTP. The heterogeneity analysis further shows that this effect is more pronounced in non-state-owned enterprises, high supply chain integration, high industry competition, and non-high-polluting industries. The mechanism analysis shows that SCD promotes EGTP by enhancing an enterprise’s adaptive, absorptive, and innovative capabilities. Further analysis demonstrates that the spillover effects of SCD have a more pronounced impact on upstream suppliers’ EGTP. These insights offer theoretical and practical guidance for enterprise managers and policymakers seeking to leverage SCD in sustainable environmental practices.